Chondroprotective activity of N-acetylglucosamine in rabbits with experimental osteoarthritis. Issue 1 (17th December 2004) - Shikhman, A R; Amiel, D; D'Lima, D; Hwang, S-B; Hu, C; Xu, A; Hashimoto, S; Kobayashi, K; Sasho, T; Lotz, M K
Abstract : Objective: To examine the therapeutic efficacy of N -acetylglucosamine (GlcNAc) in rabbits with experimental osteoarthritis (OA). Methods: Experimental OA was induced in rabbits by anterior cruciate ligament transection (ACLT). In the first study, rabbits (six in each group) received intramuscular injections of GlcNAc or normal saline three times a week starting 1 week postoperatively. In the second study, rabbits (eight in each group) were injected intra-articularly with GlcNAc (either once or twice a week) or normal saline. In the third study, rabbits (seven in each group) were injected intra-articularly twice a week with either GlcNAc, hyaluronan, or normal saline. Animals were killed 8 weeks after ACLT for macroscopic and histological assessment of the knee joints. Results: Intramuscular administration of GlcNAc in rabbits with experimental knee OA did not show chondroprotective effects but showed mild anti-inflammatory activity. In contrast, intra-articular administration of GlcNAc twice a week reduced cartilage degradation. Additionally, intra-articular GlcNAc also suppressed synovitis. Once a week intra-articular injections of GlcNAc did not demonstrate therapeutic efficacy. The chondroprotective efficacy of GlcNAc was better than that of viscosupplementation treatment with hyaluronan. Conclusion: Intra-articular GlcNAc has chondroprotective and anti-inflammatory activity in experimental OA.